Kinematics Conceptual Understanding: Interpretation of Position Equations as a Function of Time - Muhammad Reyza Arief Taqwa; Lugy Rivaldo (Pascasarjana Universitas Negeri Malang (UM), 2018)
Abstract: This article aims at describing the ability of 48 students of physics education in determining the distance traveled, average speed, and acceleration of position functions. To achieve these objectives, three reasoned multiple choice questions were used. The question is part of 20 standard test questions that are used to measure understanding of student mechanics concepts in the Basic Physics course. The study was conducted using a survey method. Data were obtained from student responses in answering questions. Claims of student understanding were seen from the choice of answer options and reasons given. The results of the study indicate that students still have many wrong assumptions regarding x(t), namely as a displacement; determine the distance from x(t) by adding the position of each unit of time and adding the initial and final positions; and assume that acceleration (-) is slowing down.Key Words: conceptual understanding, function of position, kinematicsAbstrak: Artikel ini bertujuan untuk mendeskripsikan kemampuan 48 mahasiswa pendidikan fisika dalam menentukan jarak tempuh, kecepatan rata-rata, dan percepatan dari fungsi posisi. Untuk mencapai tujuan tersebut digunakan tiga soal pilihan ganda beralasan. Soal tersebut merupakan bagian dari 20 soal tes standar yang digunakan untuk mengukur pemahaman konsep mekanika mahasiswa pada mata kuliah Fisika Dasar. Penelitian dilakukan dengan menggunakan metode survei. Data diperoleh dari respon mahasiswa dalam menjawab soal. Klaim pemahaman mahasiswa dilihat dari pilihan opsi jawaban dan alasan yang diberikan. Hasil penelitian menunjukkan bahwa mahasiswa masih banyak memiliki anggapan yang salah terhadap x(t) yakni sebagai perpindahan; menentukan jarak tempuh dari x(t) dengan men-jumlah posisi setiap satuan waktu, dan menjumlah posisi awal dan akhir; dan menganggap bahwa percepatan (-) sebagai perlambatan.Kata kunci: pemahaman konsep, fungsi posisi, kinematika